Practical limitations of Talbot imaging with microlens arrays - Lindlein, Norbert; et al. (Journal of Optics A: Pure and Applied Optics, 1997)
The Talbot effect which also appears for the foci of microlens arrays can, in principle, be used for array illuminators. In particular, the multiplication of the foci in the fractional Talbot planes seems to be promising. Certainly, in practice there are three effects which limit the application of the fractional Talbot effect for microlens arrays. Theoretical, numerical and experimental results are given to demonstrate these limitations. © 1997 IOP Publishing Ltd.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.practi